Functional connectivity of brain regions for self‐ and other‐evaluation in children, adolescents and adults with autism. Issue 4 (11th January 2016) - Burrows, Catherine A.; Laird, Angela R.; Uddin, Lucina Q.
Abstract: Developing strong ties between oneself and others lays the foundation for developing social competence. Neuroimaging studies have consistently identified specific cortical midline regions activated during evaluative judgments about the self and others. Individuals with autism spectrum disorder (ASD) process self‐relevant information differently from their peers, both behaviorally and at the neural level. We compared resting‐state functional connectivity (rsFC) of regions involved in self‐referential (e.g. medial prefrontal cortex; mPFC) and other‐referential (e.g. posterior cingulate cortex; PCC) processing between neurotypical individuals and individuals with ASD in three age cohorts using regions of interest (ROIs) identified through an activation likelihood estimation meta‐analysis. Typically developing children demonstrated greater connectivity within the midline self‐ and other‐referential networks compared with age‐matched children with ASD. No group differences in rsFC of mPFC or PCC emerged between typically developing adolescents and adolescents with ASD. Neurotypical adults exhibited stronger rsFC of the PCC with orbitofrontal cortex compared with adults with ASD. Developmental differences in functional connectivity between areas underlying self‐ and other‐referential thought may explain altered developmental trajectories in the understanding of self and others in individuals with ASD. Abstract : Individuals with autism spectrum disorder (ASD) demonstrate differences in self‐referential processing, which may contribute to reduced understanding of themselves and others. We examined functional connectivity of brain regions underlying self and other‐referential processing in individuals with ASD across development. Children with ASD demonstrated functional underconnectivity of both regions of interest compared with typically developing individuals, while older individuals showed fewer group differences.